2023
DOI: 10.3390/biomedicines11051496
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Inhibitor-Induced Colitis: An Update

Giuseppe Losurdo,
Daniele Angelillo,
Nicolas Favia
et al.

Abstract: Immunotherapy with immune checkpoint inhibitors (ICIs) nowadays has indications for several solid tumors. The current targets for ICIs are CTLA-4, PD-1, and PD-L1 receptors. Despite the clinical advantages derived from ICIs, a variety of side effects are linked to overstimulation of the immune system. Among these, ICI-related colitis is one of the most common, with a disabling impact on the patient. Diarrhea, abdominal pain, abdominal distension, cramping, and hematochezia are the most common ICI enterocolitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The median time to resolution of diarrhea from the first infliximab dose was 8.5 ± 16.4 days. Other studies have also demonstrated a similarly high clinical remission rate (87%) following the addition of infliximab to steroids for immune-mediated diarrhea [ 35 ].…”
Section: Discussionmentioning
confidence: 93%
“…The median time to resolution of diarrhea from the first infliximab dose was 8.5 ± 16.4 days. Other studies have also demonstrated a similarly high clinical remission rate (87%) following the addition of infliximab to steroids for immune-mediated diarrhea [ 35 ].…”
Section: Discussionmentioning
confidence: 93%
“…PD-L1 protein inhibits colonic inflammation and colitis in mice 24 . A major adverse effect of PD-(L)1 ICI immunotherapy in human cancer patients is ulcerative colitis 22,3841 . PD-L1 therefore plays an essential role in protecting colorectal epithelium from colonic inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Off-label use of infliximab and vedolizumab has been associated with good clinical responses. This patient reported not having a good response to Infliximab, but vedolizumab seemed effective on gastrointestinal symptoms [ 11 ].…”
Section: Discussionmentioning
confidence: 99%